2020
DOI: 10.3390/ijms21197159
|View full text |Cite
|
Sign up to set email alerts
|

Value of Glucosylsphingosine (Lyso-Gb1) as a Biomarker in Gaucher Disease: A Systematic Literature Review

Abstract: The challenges in the diagnosis, prognosis, and monitoring of Gaucher disease (GD), an autosomal recessive inborn error of glycosphingolipid metabolism, can negatively impact clinical outcomes. This systematic literature review evaluated the value of glucosylsphingosine (lyso-Gb1), as the most reliable biomarker currently available for the diagnosis, prognosis, and disease/treatment monitoring of patients with GD. Literature searches were conducted using MEDLINE, Embase, PubMed, ScienceOpen, Science.gov, Biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
70
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 132 publications
(478 reference statements)
9
70
0
4
Order By: Relevance
“…All analysed plasma samples were below the reference cut-off value for normal lyso-Gb1 level (Table A.3). The extremely low lyso-Gb1 levels are in line with the data previously reported on healthy controls [ 6 , 27 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…All analysed plasma samples were below the reference cut-off value for normal lyso-Gb1 level (Table A.3). The extremely low lyso-Gb1 levels are in line with the data previously reported on healthy controls [ 6 , 27 ].…”
Section: Resultssupporting
confidence: 92%
“…Although four out of five patients were on enzyme replacement therapy (ERT) at the time of sample donation, lyso-Gb1 levels were above the assay-specific thresholds in all study subjects ( Table 2 ) which is line with the data in the literature [ 27 ]. Some variation was observed between the results obtained from the plasma and DBS samples with DBS samples showing 1.2–2.2 times higher lyso-Gb1 concentrations compared with frozen plasma samples ( Table 2 ).…”
Section: Resultssupporting
confidence: 86%
“…Moreover, an in vitro inhibitory GD model demonstrated that PBMC differentiated into osteoclasts with higher rate support the finding that GD patients with active bone disease formed more osteoclasts [32]. Thus, altered RANKL/RANK/OPG triad plays an integral role in GD bone pathology [2,20] In the present study, RANKL was elevated in 51% of the patients with GD. However, elevated plasma RANKL only correlates with osteopenia, but not osteoporosis, suggesting that the acceleration of osteoclast differentiation occurs before the onset of osteoporosis.…”
Section: K E L I G a N D 1supporting
confidence: 84%
“…We think that this finding is relevant to understanding the pattern of events that occur in GD bones. Because the significant correlation was verified between TRAP5b and Lyso-Gb1 and correlations between lyso-Gb1, CHITO or CCL18 were observed in several clinical studies [20], we postulate that Lyso-Gb1 is the primary contributor to TRAP5b activation, not CHITO or CCL18. A possible mechanism underlying activation expression of TRAP5 in osteoclasts is Gb1 accumulation in bone marrow cells, including monocytes/macrophages precursors cells and osteoclasts.…”
Section: K E L I G a N D 1mentioning
confidence: 64%
See 1 more Smart Citation